From Group Work to Independent Writing: Enhancing Students’ Analytical Exposition Texts through Task-Based Learning - Fauzia Nurmalasari; Windy Citra Negara; Linda Mayasari (PROCEEDING UMSURABAYA, 2026)
This study aims to investigate the extent to which the implementation of the Task-Based Learning (TBL) model can enhance the ability of Grade XI students at a public senior high school in Surabaya to write analytical exposition texts. Conducted as a Classroom Action Research over ten weeks, the study comprised three cycles. The first two cycles applied the Project-Based Learning (PjBL) approach, while the third cycle introduced TBL as the main instructional intervention. Each cycle followed the stages of planning, action, observation, and reflection. Data were collected through writing assessment rubrics, classroom video recordings, and teacher reflection sheets. The findings revealed that although collaborative methods like PjBL encouraged initial engagement, they were insufficient in fostering independent writing skills. In contrast, the application of TBL in the third cycle, featuring context-rich, differentiated writing tasks conducted without gadget use, significantly improved students’ abilities in constructing arguments, organizing ideas, and using linguistic features accurately. The average student score rose to 75.78, with 55.56% of students reaching the minimum target score of 75, thus meeting the study’s success criteria. Additionally, student engagement improved markedly, particularly in focus, initiative, and language accuracy. These findings indicate that Task-Based Learning is an effective instructional approach for developing analytical exposition writing skills at the secondary level, especially when supported by leveled tasks and structured formative assessment.